2009
DOI: 10.1002/anie.200804199
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Redox‐Induced Structural Isomerization of the Pentagonal Bipyramidal Complexes [W(CN)5(CO)2]3− and [W(CN)5(CO)2]2−

Abstract: There has been a surge of interest in the use of cyanometalate complexes for the synthesis of magnetic molecules [1] and solids.[2] The variation of the metal electron configuration and coordination geometry enables adjustment of magnetic properties, such as the spin ground state, magnetic anisotropy, and the strength of the exchange coupling. Second-and thirdrow transition-metal ions are of particular interest, owing to a large magnetic anisotropy stemming from spin-orbit coupling, as well as to their diffuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…27,28 Somewhat less anisotropic g was observed for a PBP W III derivative with mixed carbonyl/cyanide ligand set, cis -[W(CN) 5 (CO) 2 ] 2− , but EPR was recorded in solution. 29…”
Section: Transition Metal Ions With a Pentagonal Bipyramidal Coordina...mentioning
confidence: 99%
“…27,28 Somewhat less anisotropic g was observed for a PBP W III derivative with mixed carbonyl/cyanide ligand set, cis -[W(CN) 5 (CO) 2 ] 2− , but EPR was recorded in solution. 29…”
Section: Transition Metal Ions With a Pentagonal Bipyramidal Coordina...mentioning
confidence: 99%
“…41 The range found for v(CN) bands in homoleptic 26,32,33 and mixed ligand 28,59 Labeling studies of the cis/trans isomers of [W-(CN) 5 (CO) 2 ] 3− showed that backbonding to cyano ligands is more effective in the pentagonal plane, leading to lower stretching frequencies compared to the axial cyano coordination. 63 The octahedral Mo center in the isostructural 3 and 4 shows lower stretching frequencies for its cyano ligands compared to the square pyramidal geometry Mo center in the isostructural 2 and 5. The band at 2134 cm −1 in 4 is attributed to the terminal SCN − ligand.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Our attempts to reproduce the synthesis of the [W II (CN) 7 ] 2À anion led only to K 4 [W IV (CN) 8 ], which has also been confirmed by other groups. [15] Herein we report the first genuine heptacyanotungstate salt which was characterized by crystallography,s pectroscopy,a nd SQUID magnetometry.…”
mentioning
confidence: 99%